MOTYWACJA I NASTAWIENIA POLSKICH UCZNIÓW DO NAUKI JĘZYKA NIEMIECKIEGO W KONTEKŚCIE RÓŻNIC REGIONALNYCH I POSTRZEGANIA SPOŁECZEŃSTWA NIEMIECKIEGO - Mackiewicz, Maciej (Neofilolog, 2019)
The purpose of the article is to present the motivation and attitude of Polish students towards learning German. The analysis presented is based on research conducted by the author in junior and senior high schools throughout Poland. The findings indicate that the predominant motive for learning German is instrumental. Motivation connected with communication is of less importance in the east of Poland than in the western part of the country. Motivation concerning the culture of German speaking countries does not seem to be relevant for Polish students. There is a strong correlation between increasing and decreasing motivation to learn German and the image of a German person and the attitude towards the German nation: those students who are positively motivated to learn the language present an extremely positive attitude towards German society, while those with lower motivation exhibit strong prejudice against Germans.